Pengaruh Self Efficacy, Employee Engagement, dan Servant Leadership Terhadap Organizational Citizenship Behaviour Dalam Meningkatkan Kinerja Tenaga Kependidikan Perguruan Tinggi Swasta di Purwokerto - Amin Budiastuti; Susanti Budiastuti (Jurnal HUMMANSI (Humaniora, Manajemen, Akuntansi), 2018)
The aims of the research were to examine the influence of self efficacy, employee engagement, servant leadership, and organizational citizenship behavior on educational staffs’ job performance. The research problem was how to increase the job performance of educational staffs through self efficacy, employee engagement, servant leadership, and organizational citizenship behavior. This research was conducted at the Private Higher Education in Purwokerto by the member of respondents was 150 which was determined by employing cluster random sampling method. Data were collected by distributing a questionnaire. Processing data used Structural Equation Modeling (SEM) by the software Analysis of Moment Structure (AMOS). The result of analysis could be summarized as follows: Self efficacy, employee engagement, servant leadership and organizational citizenship behavior positively and significantly influenced to the job performance of staffs education. Implication of the findings indicated that to increase staffs education’ job performance, the management should more increase self efficacy, employee engagement, servant leadership, and organizational citizenship behavior.